ANALISIS FAKTOR-FAKTOR INTERNAL PERUSAHAAN YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN PT. PETRO CENTRAL GRESIK - Johanes F. X. Susanto Soekiman (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2005)
Human as source, as generally and their live looking for happiness while constitute of equation from live satisfaction. Every individual has satisfaction level while different – appropriate with value – has been valid in their self. More many aspects in the job while equation with those individual desire so more lower of satisfaction level that he feels. Satisfaction work according Herzberg (1957:107) configured to be 2 category that is: satisfaction or motivator and dissatisfies or hygiene factor. Satisfies is factors as source of satisfied work configure: opportunity achievement, confession, responsibility, work while more challenge and dissatisfies configure: work condition, salary/ fee, supervision/ leadership style while constitute of dissatisfies work. To increase productivity and effective work of employ the researcher adopt problem satisfied work of employ PT. Petro Central Gresik. Research while writer has been done with used analyst factor from program SPSS. Result finding variable while dominan affect work satisfied employ is salary variable/ fee (X2) with loading 0,86. Beside that influenced by six other variable that is in a series: variable of leadership style with loading 0,8; variable of work condition with loading 0,78; variable working while more challenge with loading 0,77; and variable confession with loading 0,74.Based on that finding, the researcher suggest for PT. Petro Central Gresik to increase satisfaction work of employ, where more give attention is: the leader of company should cooperate to increase satisfaction work of employ as whole, this very important to maximize result, because higher of work satisfaction employ could be increase productivity and effective work of employ, so leader of company holding on 2 core factor and 7 variable, with stress of core factor also variable while dominant influenced about work satisfaction, so can increase that productivity and effective work.